Recent development of heat and power generation using renewable fuels: A comprehensive review. (September 2022) - Montazerinejad, H.; Eicker, U.
Abstract: With the switching from fossil to renewable fuels, a wide range of cogeneration technologies needs to be re-assessed to analyze their efficiency, lifetime, and maintenance performance for new fuels. Depending on the application, efficiency priorities, and power range, different cogeneration technologies have been compared in this study. Fuel cells provide the highest efficiency and lowest emissions, but costs remain high, and their lifetime is lower than gas turbines. They can be used in aviation because of the lowest fuel consumption in cruise and stationary states; however, they are limited to short-range flights because refueling aircraft poses serious hydrogen leakage risks, and insulated storage tanks of hydrogen are excessive in volume and weight. Like fuel cells, micro-gas turbines and Stirling engines are used for lower power, while they have lower electrical efficiency (30% and 15% vs. 50% fuel cell efficiency for 100 kW). For large-scale applications, gas turbines and internal combustion engines are used, with lower cost, and faster ramp-up times as an advantage of ICE, while emissions are lower for GT. Using hydrogen in such systems increases efficiencies due to the higher heating value, while syngas performs less well but offers low-cost solutions, and existing infrastructure can be used. Additional cost occurs due to other hydrogen infrastructure, storage, leakage, and flame flashback risk prevention. In conclusion, cogeneration technologies offer ample scope for low emission, reliable and flexible power in future renewable energy systems and need to be carefully chosen depending on the application, power range, and performance goals. Highlights: A comprehensive review of CHP systems driven by renewable fuels is executed. Cogeneration systems are classified based on their kinds of cycles. The benefits of using decentralized CHP systems against centralized ones are outlined. Prime movers are compared based on thermodynamic, economic, and environmental indicators. The production, storage, and thermophysical properties of renewable fuels are presented.